Can we mandate partnership working? Top down meets bottom up in structural reforms in Scotland and Norway. Issue 2 (9th March 2018) - Huby, Guro Øyen; Cook, Ailsa; Kirchhoff, Ralf
Abstract : Purpose: Partnership working across health and social care is considered key to manage rising service demand whilst ensuring flexible and high-quality services. Evidence suggests that partnership working is a local concern and that wider structural context is important to sustain and direct local collaboration. "Top down" needs to create space for "bottom up" management of local contingency. Scotland and Norway have recently introduced "top down" structural reforms for mandatory partnerships. The purpose of this paper is to describe and compare these policies to consider the extent to which top-down approaches can facilitate effective partnerships that deliver on key goals. Design/methodology/approach: The authors compare Scottish (2015) and Norwegian (2012) reforms against the evidence of partnership working. The authors foreground the extent to which organisation, finance and performance management create room for partnerships to work collaboratively and in new ways. Findings: The two reforms are held in place by different health and social care organisation and governance arrangements. Room for manoeuvre at local levels has been jeopardised in both countries, but in different ways, mirroring existing structural challenges to partnership working. Known impact of the reforms hitherto suggests that the potential of partnerships to facilitate user-centred care may be compromised by an agenda of reducing pressure on hospital resources. Originality/value: Large-scale reforms risk losing sight of user outcomes. Making room for collaboration between user and services in delivering desired outcomes at individual and local levels is an incremental way to join bottom up to top down in partnership policy, retaining the necessary flexibility and involving key constituencies along the way.